Assembling the Multitude: Material Geographies of Social Movements from Oaxaca to Occupy. (June 2014) - Arenas, Iván
In light of the abstract theorizations of scholars of transnational social movement networks—as exemplified by Hardt and Negri's Multitude —in this paper I argue for the power of grounded, material engagements with the practices of protest of social movements to transform not just political spaces, but our theoretical landscapes. I compare the practice of setting up and maintaining encampments in the Oaxaca and Occupy movements to argue that the spatial dynamics of occupation in a tent city fuels the distinctive style of participatory politics of the assembly, providing a creative means to transform confrontation into cooperation. A point of departure for this comparison is my assertion that the political difference made by these social movements lies not just in whether or not they achieved their political goals, but in the kind of intervention that the physical fact of occupying a public space entails in normative understandings of politics and public spaces.